Evaluation of the Efficacy of Tenofovir Alafenamide in Patients with Low-Level Viremia Under Chronic Hepatitis B Treatment - Tahmaz, Alper; Dikmen, Merve Yildiz; Yildirim, Figen; Kaygusuz, Turkkan Ozturk; Karabay, Oguz; Celen, Mustafa Kemal; Cabalak, Mehmet (Mdpi, 2025)
In this multicenter, retrospective study involving 62 patients, we investigated whether switching from entecavir (ETV) or tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) represents a superior treatment strategy for patients with chronic hepatitis B (CHB) experiencing low-level viremia (LLV). The study determined that TAF significantly improved both virological and biochemical outcomes. At 48 weeks, the complete virological response (CVR) rate was 77.8% for those who switched from ETV and 81.8% for those who switched from TDF, with Hepatitis B virus deoxyribonucleic acid (HBV DNA) negativity reaching 81% by month 12. Additionally, significant normalization of liver enzymes, albumin, and platelet counts was observed across the cohort. While the switch from TDF was associated with a significant increase in triglycerides and high-density lipoprotein (HDL) and a decrease in estimated glomerular filtration rate (eGFR), no such changes were detected in the ETV group. This evidence suggests that TAF provides robust virological control in LLV patients and is associated with favorable biochemical improvements. However, due to the study's limitations, the strong assertion that TAF promotes the regression of liver fibrosis and reduces the risk of hepatocellular carcinoma (HCC) must be interpreted with caution.
Keywords: low level viremi; Hepatitis B; tenofovir; tenofovir alafenamide (TAF); entecavir; efficiency; hepatocellular carcinoma